A tetraphenylethylene-based covalent organic polymer for highly selective and sensitive detection of Fe3+ and as a white light emitting diode. Issue 82 (26th September 2019) - Zhang, Han; Zhou, Jie; Shan, Guo-Gang; Li, Guang-Fu; Sun, Chun-Yi; Cui, Dong-Xu; Wang, Xin-Long; Su, Zhong-Min
Abstract : A new COP is synthesized, exhibiting excellent performance as an Fe 3+ sensor with a LOD of 23.5 ppb, and solid-state illumination. Abstract : A newly prepared tetraphenylethylene-based (TPE-based) covalent organic polymer (COP) named COP-1 exhibits high selectivity for sensing Fe 3+ and the limit of detection (LOD) for Fe 3+ is 0.42 μM, which is lower than the reported metal-free porous polymers. Furthermore, a WLED is fabricated and the CIE coordinates are (0.32, 0.33), very close to pure white light. The COP-1 shows potential applications in biosensors of Fe 3+ and preparation of WLEDs.